Expression of Estrogen Receptors Alpha (ER-α), Beta (ER-β), and G Protein-Coupled Receptor 30 (GPR30) in Testicular Tissue of Men with Klinefelter Syndrome - Bernardino, R. L.; Alves, M. G.; Silva, J.; Barros, A.; Ferraz, L.; Sousa, M.; Sá, R.; Oliveira, P. F. (Hormone and Metabolic Research, 2016)
Men with Klinefelter syndrome (KS) present severe hormonal dysregulation, particularly elevated serum estradiol concentration. Estrogens act through specific receptors and regulate testes development and spermatogenesis. Herein, we evaluated GPR30, ERα, and ERβ mRNA expression in testis of KS men and men with 46XY karyotype by reverse transcriptase and quantitative PCR. ERβ transcripts are the most abundant in testicular tissue of 46XY men. Notably, testicular GPR30 transcription in KS men was approximately 12 times higher. Since GPR30 is essential to mediate estrogen effects over steroidogenesis, our data illustrate that GPR30 may underpin the testicular alterations observed in KS men.
Keywords: estrogen receptors; Klinefelter syndrome; spermatogenesis; fertility